Legendary Culinary Tourism in Jakarta, Indonesia - Sulistiyo, Tri Djoko; Gantina, Devita; Haryono, Joko; Riyadi, Agus; Irfal, Irfal (Institut Pariwisata Trisakti, 2024)
This research explores legendary Jakarta culinary delights reflecting local traditions, global influences, and the city's cultural identity. The study aims to identify and analyse iconic restaurants such as Ragusa Es Italia and Nasi Goreng Kebon Sirih. The methods include semi-structured interviews, participant observation, and document collection to understand culinary delights' experience, history, and social impact. The results identified eight legendary restaurants, each significantly contributing to Jakarta's culinary culture. The culinary experience at these places is not just about the food but also strengthens social interactions between diners, creating connected communities. Analysis shows that the restaurant is a custodian of cultural and historical values, connecting different generations. The conclusion is that the culinary legend not only serves delicious food but also builds the city's identity. Means for preserving culinary heritage include collaboration between government, communities, and entrepreneurs and training programs for the younger generation to maintain traditional cooking techniques. Hopefully, this research will become a reference in developing culinary studies and preserving cultural heritage in Jakarta. Keywords: legendary culinary delights, Jakarta, cultural identity, social interaction, heritage preservation